2020
DOI: 10.1001/jamaoto.2020.0225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Incidence of Other Cranial Neuropathies in Patients With Postviral Olfactory Loss

Abstract: IMPORTANCE Postviral olfactory loss is a common cause of olfactory impairment, affecting both quality of life as well as overall patient mortality. It is currently unclear why some patients are able to recover fully after a loss while others experience permanent deficit. There is a lack of research on the possible association between postviral olfactory loss and other cranial neuropathies.OBJECTIVE To evaluate the incidence of other cranial nerve deficits in patients with postviral olfactory loss and determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…These findings contrast with an epidemiological study where a correlation was found between hearing loss and olfactory dysfunction, but infection, in particular congenital, was not considered as an influential factor [24]. The incidence of cranial neuropathies is higher in patients with post-viral olfactory loss compared to a control population [25]; however, we found no difference for the olfactory score between children presenting neurological manifestations and those without neurological involvement. These findings suggest that peripheral (audiovestibular) and central (cerebral) lesions are independent and that neurological damage did not induce vulnerability to olfactory dysfunction in our sCMV infants.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings contrast with an epidemiological study where a correlation was found between hearing loss and olfactory dysfunction, but infection, in particular congenital, was not considered as an influential factor [24]. The incidence of cranial neuropathies is higher in patients with post-viral olfactory loss compared to a control population [25]; however, we found no difference for the olfactory score between children presenting neurological manifestations and those without neurological involvement. These findings suggest that peripheral (audiovestibular) and central (cerebral) lesions are independent and that neurological damage did not induce vulnerability to olfactory dysfunction in our sCMV infants.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, central processing pathways related to smell may be damaged through direct transmission of the virus to (Charles et al, 1995;Reiss et al, 1998;Doty, 2003;van Riel et al, 2015). Additionally, paresis/paralysis of the cranial nerves and history of neurological disease are associated with PVOD more than other olfactory disorders such as chronic rhinosinusitis (Jitaroon et al, 2020). Nevertheless, the decrease in sensory input leads to shrinkage of central olfactory areas such as the olfactory bulb that has both upstream and downstream effects (Mueller et al, 2005;Rombaux et al, 2006;Yao et al, 2018).…”
Section: Postviral Chemosensory Clinical Manifestationsmentioning
confidence: 99%
“…Reports show an abundance of nasal epithelial cells expressing cellular receptors and proteases needed for viral entry, i.e. angiotensin-converting enzyme 2 (ACE-2) and transmembrane serine protease 2 (TMPRSS2) ( (Brann et al, 2020;Chen et al, 2020;Gupta et al, 2020;Hoffmann et al, 2020;Sungnak et al, 2020) along with patients having neurological conditions to SARS-CoV-2 (Mao et al, 2020) and other infections leading to PVOD (Jitaroon et al, 2020). Although reports on OTDs in COVID-19 are being published or archived every day, the lack of follow-up studies to determine the dynamics of chemosensory changes in the disease and its reversibility over time are not currently available.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…A second set of HCoVs are more pathogenic and include the etiological agents of the two epidemics occurring earlier this century, namely, the severe acute respiratory syndrome (SARS-CoV) and the Middle East respiratory syndrome (MERS-CoV) viruses. The ongoing outbreak of coronavirus disease 2019 (COVID- 19) completely different functions in the cell, to serve as binding partners. Binding of viruses to these adapted molecules, usually transmembrane enzymes, is the first step in viral infection.…”
Section: ■ Introductionmentioning
confidence: 99%